Effectiveness of a hybrid practice-based training program for community-based elderly caregivers in Chiang Rai during the COVID-19 pandemic - Ananya Eusawat; Watcharapong Ruankham; Rawipat Pullap; Piyaporn Tamesak; Nattra Somkamlang (Journal of Public Health and Development, 2026)
The study aimed to evaluate the effectiveness of the program, which was a hybrid practice-based training program for community-based elderly caregivers in Chiang Rai during the COVID-19 pandemic. It was a mixed-methods design. Research instruments included caregiver knowledge and skill assessment and the hybrid practice-based caregiver training program adapted for the COVID-19 situation. Phase 1 involved program refinement based on feedback from 39 stakeholders. Phase 2 examined the influence of individual learning modules on caregiving skills. The sample consisted of 165 purposively selected caregivers from 16 districts. The sample size was determined using the Bentler and Chou ratio. Phase 3 evaluated program effectiveness in 60 caregivers using a two-group pretest–posttest design. The sample size was calculated based on a large effect size, α = 0.05, and power = 0.80. Data analysis comprised qualitative synthesis from focus-group discussions, multiple regression analysis, t-test, Mann–Whitney U test and the Wilcoxon signed-rank test. The results from the multiple regression analysis showed that all learning modules were significant predictors of scores of caregiving skills (R2 = 0.57, p < .001). In the quasi-experimental phase, post-training scores of the experimental group on knowledge and skills were significantly greater than those of the control group with a large effect size (knowledge: t = 14.13, p < .001, r = 0.85; caregiving skills: U = 0.00, p < .001, r = 0.87). Therefore, the hybrid practice-based caregiver training program with mentorship could improve caregiving knowledge and skills. However, larger-scale studies with longer follow-up periods are needed before broader implementation.